2019
DOI: 10.5815/ijmsc.2019.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Bullying Detection and Classification using Multinomial Naïve Bayes and Fuzzy Logic

Abstract: The advent of different social networking sites has enabled people to easily connect all over the world and share their interests. However, Social Networking Sites are providing opportunities for cyber bullying activities that poses significant threat to physical and mental health of the victims. Social media platforms like Facebook, Twitter, Instagram etc. are vulnerable to cyber bullying and incidents like these are very common now-a-days. A large number of victims may be saved from the impacts of cyber bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The proposed hybrid approach involves selecting the unigrams with multinomial naïve bayes classifier for classification. The accuracy of the processed approach is shown in figure (2). The confusion matrix of the classifier shows that the sentiment is classified correctly as positive/negative.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed hybrid approach involves selecting the unigrams with multinomial naïve bayes classifier for classification. The accuracy of the processed approach is shown in figure (2). The confusion matrix of the classifier shows that the sentiment is classified correctly as positive/negative.…”
Section: Resultsmentioning
confidence: 99%
“…Fuzzy logic is used to determine the strength of bully. The data set used is collected from the approach used by Akhter, Arnisha from facebook data [2]. It is shown that naïve bayes classifier has more accuracy than support vector machine model (SVM) and less run time.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zaib et al [16], users may exhibit varied and unpredictable behaviors on social media, and therefore, the best approach to track those behaviors is social media mining and behavior analytics. Akther et al [17] suggested that cyberbullying should also be evaluated in relation to terror messages and the study of Akther et al [17] presented a training algorithm that classifies the content of cyberbullying into three sub-categories of harassment, racism, and shaming.…”
Section: Problem Statementmentioning
confidence: 99%
“…Almost all of them are not realized, if there is a possibility or a dangerous action will occur. His concern is that social media is a place and target for finding someone who will be the target of crime, one of which is cyberbullying [3]. Negative actions in cyberspace such as insulting, harassing, ridiculing and even threatening the victim.…”
Section: Introductionmentioning
confidence: 99%